Prudential Responses to De Facto Dollarization - Ize, Alain (IMF Working Papers; Working Paper ;, 2004)
We develop a theoretical framework that encompasses four distinct motives for dollarization and discuss appropriate policy responses to help contain dollarization and its attendant risks. "Moral hazard" dollarization provides a clear case for prudential policy activism. However, prudential reform will have only a limited impact on dollarization when the main culprits are fear of floating and lack of monetary credibility. In such cases, a concerted and comprehensive reform agenda, including market-oriented and institutional reforms, would be needed to shift the balance of risks in favor of the domestic currency. While quantitative limits on dollarization could also be used to speed up de-dollarization, risks could be high.